2010
DOI: 10.1371/journal.pone.0014126
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight, Childhood Body Mass Index and Risk of Coronary Heart Disease in Adults: Combined Historical Cohort Studies

Abstract: BackgroundLow birth weight and high childhood body mass index (BMI) is each associated with an increased risk of coronary heart disease (CHD) in adult life. We studied individual and combined associations of birth weight and childhood BMI with the risk of CHD in adulthood.Methods/Principal FindingsBirth weight and BMI at age seven years were available in 216,771 Danish and Finnish individuals born 1924–1976. Linkage to national registers for hospitalization and causes of death identified 8,805 CHD events durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 51 publications
1
81
0
2
Order By: Relevance
“…Andersen et al (2010), found that birth weight and BMI at the age of seven appears to exercise mutually independent effects on the risk of cardiovascular disease [1]. They described that children with a combination of low birth weight and relatively high BMI had a cardiac risk of 44%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andersen et al (2010), found that birth weight and BMI at the age of seven appears to exercise mutually independent effects on the risk of cardiovascular disease [1]. They described that children with a combination of low birth weight and relatively high BMI had a cardiac risk of 44%.…”
Section: Resultsmentioning
confidence: 99%
“…Andersen and co-workers described that higher BMI in children with very low birth weight is associated with higher cardiac risk [1].…”
Section: Introductionmentioning
confidence: 99%
“…24 It has been postulated that rapid weight gain and obesity in childhood are associated with an increased risk of hypertension and type 2 diabetes in adulthood, which are risk factors for kidney disease. 11,12 In a retrospective cohort study among 80 children with proteinuric kidney disease, obese children who were born preterm had an increased risk of progression of kidney disease compared with obese children who were born at term, suggesting an additive risk of obesity and prematurity in the risks for progression of kidney disease. 25 Experimental studies have shown that adequate feeding of low birth weight rats could restore nephron numbers to normal and that overfeeding of these rats led to low nephron numbers, hypertension, and renal injury.…”
Section: Fetal and Early Childhood Growth And Childhood Kidneymentioning
confidence: 99%
“…1 Longitudinal studies suggested that the associations of low birth weight with hypertension were stronger in subjects with rapid weight gain in childhood, but results are inconclusive. 11,12 A similar growth pattern has not been identified as a risk factor for kidney diseases yet.…”
mentioning
confidence: 99%
“…Elevated BMI in childhood is strongly associated with increased risk of coronary heart disease in adulthood, as well as increased risk of acute coronary syndrome (Baker et al, 2007;Jensen et al, 2008;Andersen et al, 2010 (Krûmiòa u.c., 2007). With this variety of reference standards available, it is important for physicians to use scales that are appropriate for the evaluation of individual children, because the future management of their assigned therapy depends on precise and accurate evaluation of excess weight.…”
Section: Introductionmentioning
confidence: 99%